Reshaping Economic Geography : Implications for New EU Member States - Gill, Indermit (World Bank, Washington, DC, 2012)
The ongoing crisis should spur deeper European integration, rather than a return to the nationalism of the past. The World Development Report 2009, reshaping economic geography, spotlights several issues for new European Union (EU) member states. From 1950 to 1990, Eastern Europe was impermeable to the flow of goods, services and ideas from the West, and grew slowly. During the same period, gross domestic product (GDP) per capita in fourteen Western European economies grew at three times the pace of Eastern Europe. The drivers of West European growth were market economies, regional cooperation, and global economic integration. The European Economic Community, started by six Western European nations in 1957, continued to increase its membership with the ultimate aim of full economic and monetary integration. After the collapse of the former Soviet Union in 1991, the EU10 countries, along with Malta and Cyprus, joined the expanded European Union, an economic zone based on the principles of democracy, markets and the free mobility of goods, capital and labor. The 27country European Union has a combined population of almost 500 million people and accounts for over 30 percent of the world's GDP. But the legacy of division has meant that the EU10 countries lag considerably behind most of the other member states. While the EU10 have brought 123 million people into the European Union, they have reduced its average level of GDP per capita by an estimated 15.6 percent.